Imagine : how creativity works - Lehrer, Jonah (Edinburg, London : Canongate, 2012)
Discusses the science behind creativity and how it can be used to make cities, companies, and culture more creative.
Includes bibliographical references and index.
Booklist
Kirkus Review
Booklist, February 2012
Kirkus Review, February 2012
Adult.
Keywords: Creative ability; Creative thinking; Imagination; Creative ability; Creative thinking; Imagination